Second chances: Subprime mortgage modification and re-default - Andrew Haughwout; Ebiere Okah; Joseph Tracy (Federal Reserve Bank of New York, 2009)
Mortgage modifications have become an important component of public interventions designed to reduce foreclosures. In this paper, we examine how the structure of a mortgage modification affects the likelihood of the modified mortgage re-defaulting over the next year. Using data on subprime modifications that precede the government's Home Affordable Modification Program, we focus our attention on those modifications in which the borrower was seriously delinquent and the monthly payment was reduced as part of the modification. The data indicate that the re-default rate declines with the magnitude of the reduction in the monthly payment, but also that the re-default rate declines relatively more when the payment reduction is achieved through principal forgiveness as opposed to lower interest rates.
Keywords: G21; R31; 330; Mortgage modifications; subprime